Social Cognition in Williams Syndrome: Genotype/Phenotype Insights from Partial Deletion Patients - Karmiloff-Smith, Annette; Broadbent, Hannah; Farran, Emily K.; Longhi, Elena; D'Souza, Dean; Metcalfe, Kay; Tassabehji, May; Wu, Rachel; Senju, Atsushi; Happé, Francesca; Turnpenny, Peter; Sansbury, Francis (Frontiers in Psychology, 2012)
Identifying genotype-phenotype relations in human social cognition has been enhanced by the study of Williams syndrome (WS). Indeed, individuals with WS present with a particularly strong social drive, and researchers have sought to link deleted genes in the WS Critical Region (WSCR) of chromosome 7q11.23 to this unusual social profile. In this paper, we provide details of two case studies of children with partial genetic deletions in the WSCR: an 11-year-old female with a deletion of 24 of the 28 WS genes, and a 14-year-old male who presents with the opposite profile, i.e. the deletion of only 4 genes at the telomeric end of the WSCR. We tested these two children on a large battery of standardised and experimental social perception and social cognition tasks - both implicit and explicit - as well as standardised social questionnaires and general psychometric measures. Our findings reveal a partial WS socio-cognitive profile in the female, contrasted with a more autistic-like profile in the male. We discuss the implications of these findings for genotype/phenotype relations, as well as the advantages and limitations of animal models and of case study approaches.